The use of UML activity diagrams and the i* language in the modeling of the balanced scorecard implantation process - Haya, Mariela (2005)
Business management is a complex task that can be facilitated using different methodologies and models. One of their most relevant purposes is to align the organization strategy with the daily functioning of the organization. One of these models is the Balanced Scorecard (BSC). In this paper, we propose a modeling strategy for the BSC implantation process. We will model it using UML Activity Diagrams and Strategy Dependency models of the language i*. The Activity Diagrams allow determining the order in which involved activities must be performed, and at the same time, to identify which people has the responsability to carry them out. The Strategic Dependency model allows showing the intentional aspects of the actors involved in the most strategic activities of this process. Finally, relationships among the actors and the people involved in the BSC implantation process are modelled using again the language i*. Although this paper only considers the case study of the BSC implantation, our proposal can be generalized to other implantation processes of systems with a high strategic impact on the organization, like ERP or CRM systems.